Students' perception of quality of medical education in a medical college in west Bengal, India - Dipta Kanti Mukhopadhyay (Wolters Kluwer Medknow Publications, 2016)
Background: Students' perceived quality of educational service is an important field of educational research. Objectives: To identify the gaps in the quality of educational services as perceived by students in a medical college in West Bengal, India. Materials and Methods: In a cross-sectional study, educational quality was measured using validated SERVQUAL instrument between two randomly selected groups of undergraduate medical students (n = 179). This five-point Likert scale questionnaire measured the expectation and perception of students on 26 items under five dimensions of quality of educational services, viz., tangible (physical facilities, equipment, and appearance of personnel), reliability (accuracy and consistency of a department in providing educational services), responsiveness (eagerness to help and commitment), assurance (ability of teaching departments to earn students' confidence), and empathy (ability to communicate care and understanding). Dimension-wise difference in the mean scores for expectation and perception was calculated and was considered as quality gaps in educational services. Results: Significant negative quality gaps were noted in all five dimensions. The highest gap was found in tangible (-1.67) followed by empathy (-1.64) although the mean score of perceived quality in the dimension of empathy was the lowest (2.53). This indicates the need for improvement in physical facilities as well as behavior of teachers and staff toward students. The smallest gap was noted in the dimension of assurance (-1.29), which indicates the students' overall confidence in teaching departments regarding their management or content expertise. Conclusion: These findings underscore students' aspiration for the overall improvement of educational services that can be taken into consideration during development planning.